O empreendedorismo fazendo muito com pouco com a bricolagem social na saúde pública - Enobe, Elisabete Casimira (2023)
This work primarily focuses on social enterprises in the health sector, considering the importance of health as a structural element of the welfare state and its direct impact on improving the quality of life of the population and ensuring the right to life. However, the scarcity of resources and the difficulties faced in the sector, which often result in limitations in serving the population, are widely recognized. This study aims to investigate how social bricolage assists social enterprises in meeting public health needs. The general objective is to analyze the contribution of social bricolage so that these companies can meet the demands in the health area. To achieve this goal, the following specific objectives were established: a) Explore how social bricolage is used by health social enterprises to offer services in the current context; b) Adapt a conceptual model of social bricolage based on the social enterprises studied, in order to provide a reflective framework to improve health services. The research was carried out using a qualitative approach, with an exploratory nature, using the case study method. The analysis was descriptive and based on multiple cases, following the methodology proposed by Eisenhardt (1989). The results indicate that social bricolage enables the creation and development of health social enterprises, allowing more efficient and better quality care for the needy population compared to public health services. Furthermore, a reflective model was developed, directing actions in each component of social bricolage. The study's limitations include the diversity among the analyzed companies, requiring more in-depth analyses for each type of company, and the scarcity of specific academic references on social enterprises in the context of health services, mainly regarding the use of the components of social bricolage as support for these companies.